RELATIONSHIP BETWEEN ALONELINESS AND HARSH SUPERVISORY BEHAVIOR AMONG SMALL AND MEDIUM-SIZED ENTERPRISE OWNERS IN JAPAN: - Murakami, Yusuke; Wu, Jingxuan; Kurioka, Sumiko (Universitas Nusa Cendana, 2025)
This study examines the mediating role of anger in the relationship between aloneliness and harsh supervisory behavior (HSB) toward employees among small and medium-sized enterprise (SME) owners and the moderating effect of spirituality on this mediating relationship. We conducted an internet survey to collect responses from 800 SME owners in Japan. The final sample included data from 678 individuals. The mediation/moderated mediation analysis (BCa method, 5,000 iterations) revealed a significant mediating effect of anger in the relationship between aloneliness and HSB, whereas the moderating effect of spirituality was non-significant. These findings suggest that SME owners who perceive a lack of solitary time experience anger more frequently, leading to harsher interactions with employees. Keywords: Solitude; Occupational Stress; Workplace Aggression